The Effect of Work Discipline and Work Environment on Employee Performance at PT. Rumah Riuh Renjana, Jakarta - Endang Kustini; Sinta Sulistiani; Rini Dianti Fauzi (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the effect of work discipline on employee performance, work environment on employee performance, and the simultaneous influence of work discipline and work environment on employee performance at PT. Jakarta's boisterous home. The research method used in this study is a quantitative method with a descriptive approach. The research data was collected using a questionnaire with a population of 65 people and a sample of 65 people. The sampling technique used was the saturated sample technique. The analytical methods used are validity test, reliability test, classical assumption test, correlation coefficient, coefficient of determination, simple linear regression analysis, multiple linear regression analysis, t test and F test. Work Discipline Variable (X1) has a significant contribution to employee performance variables. (Y) of 44.6%. The Work Environment Variable (X2) has an influence on the Employee Performance variable (Y) of 44.7%. The Variable Effect of Work Discipline (X1) and Work Environment (X2) has a contribution of influence on the Employee Performance variable (Y) of 49.9%, and there is a positive and significant influence simultaneously (simultaneously) between the independent variables on the dependent variable.